On the multiwavelength spectrum of the microquasar 1E 1740.7-2942 - Bosch-Ramon, V. (2006)
Context. The microquasar 1E 1740.7-2942 is a source located in the direction of the Galactic Center. It has been detected at X-rays, soft gamma-rays, and in the radio band, showing an extended radio component in the form of a double-sided jet. Although no optical counterpart has been found so far for IE 1740.7-2942, its X-ray activity strongly points to a galactic nature. Aims. We aim to improve our understanding of the hard X-ray and gamma-ray production in the system, exploring whether the jet can emit significantly at high energies under the light of the present knowledge. Methods. We have modeled the source emission, from radio to gamma-rays, with a cold-matter dominated jet model. INTEGRAL data combined with radio and RXTE data, as well as EGRET and HESS upper-limits, are used to compare the computed and the observed spectra. Results. From our modeling, we find out that jet emission cannot explain the high fluxes observed at hard X-rays without violating at the same time the constraints from the radio data, favoring the corona origin of the hard X-rays. Also, 1E 1740.7-2942 might be detected by GLAST or AGILE at GeV energies, and by HESS and HESS-II beyond 100 GeV, with the spectral shape likely affected by photon-photon absorption in the disk and corona photon fields.